Supplementation and therapeutic use of vitamin D in patients with multiple sclerosis: Consensus of the Scientific Department of Neuroimmunology of the Brazilian Academy of Neurology - Souza, Doralina Guimarães Brum [UNESP]; Comini-frota, Elizabeth Regina; Vasconcelos, Claúdia Cristina F.; Dias-tosta, Elza (Academia Brasileira de Neurologia (ABNEURO), 2014)
A esclerose múltipla (EM) é uma doença inflamatória, autoimune, desmielinizante e degenerativa do sistema nervoso central. Estudos epidemiológicos têm identificado associações de hipovitaminose D com doenças autoimunes. O principal objetivo desta revisão é responder se há evidências que indiquem o uso terapêutico de vitamina D em monoterapia para pacientes com EM. Por meio dos sites PUBMED, EMBASE, LILACS e Scielo foram realizadas buscas usando os descritores “vitamin D”, e “multiple sclerosis” até 12/09/2013. Estudos clínicos randomizados, controlados e duplo-cegos foram selecionados para avaliar a resposta terapêutica da vitamina D na EM. Não foram encontradas evidências científicas que justifiquem o uso da vitamina D em monoterapia no tratamento da EM, na prática clínica.

Multiple sclerosis (MS) is an inflammatory, autoimmune, demyelinating, and degenerative central nervous system disease. Even though the etiology of MS has not yet been fully elucidated, there is evidence that genetic and environmental factors interact to cause the disease. Among the main environmental factors studied, those more likely associated with MS include certain viruses, smoking, and hypovitaminosis D. This review aimed to determine whether there is evidence to recommend the use of vitamin D as monotherapy or as adjunct therapy in patients with MS. We searched PUBMED, EMBASE, COCHRANNE, and LILACS databases for studies published until September 9 th , 2013, using the keywords “multiple sclerosis”, “vitamin D”, and “clinical trial”. There is no scientific evidence up to the production of this consensus for the use of vitamin D as monotherapy for MS in clinical practice.
Suplementação e uso terapêutico de vitamina D nos pacientes com esclerose múltipla: Consenso do Departamento Científico de Neuroimunologia da Academia Brasileira de Neurologia
Keywords: Vitamina D; esclerose múltipla; encefalite autoimune experimental; vitamin D; multiple sclerosis; experimental autoimmune encephalitis